The effect of geographic location and seed storage time on the content of fatty acids in stone pine (Pinus pinea L.) seeds - Özel, Halil Barış; Sevik, Hakan; Onat, Saadettin Murat; Yigit, Nurcan (BioResources, 2022)
The fatty acids content in pine seeds is important because it affects germination success and commercial value. In this study, the amount of fatty acids in the seeds of stone pine (Pinus pinea L.) was determined in seeds collected from different geographical locations and after two-year storage. The pine seeds were collected from different locations where peanut pine is densely located in the Western Black Sea Region of northern Turkey in 2019. The results showed that the content of some fatty acids (C18:1n-9, ƩMUFA, C18:2n-6, and ƩPUFA) in the seeds collected from different geographical locations did not differ significantly, but the content of others (C16:0, C18:0, C20:0, ƩSFA, and C18:3n-3) was dependent on the locations. The difference among locations was up to 40% (p < 0.05). In general, the lowest values were obtained from the seeds of Bartın Karaçaydere, and the highest values were obtained from the seeds of Bartın Çakraz and Bartın Avara locations. After two years of storage, the content of all the fatty acids in the seeds decreased based on the location, and a decrease of more than 25% in the content of some fatty acids was observed.
Keywords: Pinus Pinea; Location; Fatty Acids; Storage; Stone Pine; Waste Management and Disposal; 2. Zero hunger; 15. Life on land